Pengaruh Budaya Organisasi dan Keadilan Organisasi terhadap Kinerja ASN dengan Stres Kerja Sebagai Variabel Intervening pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Merangin - Ashadi, Edi; Zahari, M.; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to describe organizational culture, organizational justice, work stress and performance of PUPR Merangin Regency employees and to analyze the influence of organizational culture and organizational justice partially and simultaneously directly and indirectly on work stress and employee performance, as well as to analyze work stress on employee performance. To answer the purpose of this research, this research is supported by theoretical studies related to research variables, namely organizational culture, organizational justice, work stress, and performance. In addition, the author is also looking for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this study is PUPR employees totaling 93 employees with conditions in 2022. The data analysis technique used in this study is through path analysis followed by hypothesis testing through F test (Simultaneous) and t test (Partial).From the path analysis test conducted, it was found that organizational culture and organizational fairness affected work stress by 74.2% while the rest was influenced by other variants. Organizational culture and organizational justice affect 75.1% of employee performance in the Merangin Regency PUPR Office. This study concludes organizational culture, organizational fairness, work stress and employee performance in good and high conditions. In addition, organizational culture and organizational justice partially and simultaneously have a positive and significant influence on work stress and employee performance at the Merangin Regency PUPR Office. Similarly, work stress has a positive and significant influence on employee performance.